A case of local anesthetic toxicity that wasn't: lipid rescue from self-administered benzodiazepine overdose in labor. (May 2020) - Berman, D.J.
Highlights: A patient with polysubstance use disorder became unresponsive during labor. She responded to lipid emulsion therapy for presumed local anesthetic toxicity. A subsequent event in the same patient made this diagnosis unlikely. Her final diagnosis was self-supplementation with benzodiazepines during labor. Abstract: A 32-year-old G2P1 woman presented for induction of labor at term. Her past medical history included polysubstance use disorder and methadone maintenance, scant prenatal care, morbid obesity, and intimate partner violence. Her induction was progressing smoothly until the acute onset of altered mental status near to the time of delivery, several minutes after a clinician-administered epidural local anesthetic bolus for significant pain. Given concern about local anesthetic systemic toxicity, lipid emulsion was administered and resulted in an immediate and drastic clinical response. The epidural infusion bag and pump system were evaluated and found to be correct and there was no clinical suspicion of an intravascular epidural catheter. The woman remained stable and was transferred to the postpartum unit, where she experienced a similar episode of altered mental status approximately 12 h postpartum. This episode self-resolved and she was managed conservatively. Shortly after this event, it was discovered that the patient had been self-administering benzodiazepines throughout the course of her labor, in addition to her hospital staff-administered medications. Presumably, her intrapartum altered mental status was a result of self-administered benzodiazepine that was then "rescued" with lipid emulsion. This case illustrates the potential for lipid emulsion as a reversal agent for medications other than local anesthetics.